KEBUDAYAAN KERAJAAN MAJAPAHIT DALAM NASKAH DAMARWULAN: KAJIAN FILOLOGI - Livia Astuti (Universitas Wijaya Kusuma Surabaya, 2023)
The Damarwulan Manuscript is an ancient script that tells of the Majapahit Kingdom when it was led by Ratu Kencana Wungu. The story begins with the death of the last Prabu Brawijaya. Because he did not have a son to inherit his throne, Prabu Brawijaya finally passed his throne to his daughter who was only fourteen years old. The culture continued by Ratu Kencana Wungu can be seen in several texts in the manuscript. The purpose of this study is to describe the culture of the Majapahit Kingdom during the time of Ratu Kencana Wungu which is reflected in the Damarwulan manuscript. The data obtained as a source in the research is that Damarwulan's manuscript has been translated and translated by the National Library, published in book form in 2021, totaling 122 pages. The data obtained for this research is in the form of qualitative data in the form of copies of Damarwulan's manuscript translation and translation. Strengthening the cultural explanation in the Damarwulan manuscript uses a descriptive qualitative method with the knowledge of Cultural History. The results of this study are to describe the culture in the Majapahit Kingdom, namely, 1) Traditional Clothing of the Majapahit Kingdom, 2) Typical Weapons of the Majapahit Kingdom Period, 3) Interior of the Majapahit Kingdom, 4) Beliefs adopted by the Majapahit Kingdom.Keywords: Damarwulan Manuscript, Majapahit Kingdom, Culture